Kyslíkové radikály v mechanizmoch poskodenia pl'úc vyvolaného polutantmi ovzdusia - Visnovský, P; Suchánková, J; Styrandová, M (Bratislavske lekarske listy, 1997)
Ozone and nitrogen oxides are environmental pollutants especially present in smog. They are oxidants potent to cause bronchial hyperreactivity, lung fibrosis, and emphysema. Other occupational hazards are mineral dust particles (asbestos, silica) which may cause the development of inflammation and fibrosis in the lungs. Inflammatory cells (neutrophils, eosinophils, monocytes, macrophages) become activated during inflammation and produce superoxide anion radicals. Reactive oxygen species developed e.g. in smog have been recognized--at least partly--to be responsible for the observed pulmonary tissue damage. Several mechanisms leading to toxicity, including disbalance of vegetative nervous control, damage of bronchial epithelium, role of mediators of inflammation and other issues are discussed. (Fig. 1, Ref. 32.)
Keywords: Inflammation Mediators; Air Pollutants; Pulmonary Fibrosis; lidé; Humans; Dust; plíce; mediátory zánětu; smog; volné radikály; Animals; Bronchial Hyperreactivity; plicní fibróza; Lung; Smog; zvířata; prach; bronchiální hyperreaktivita; Free Radicals; látky znečišťující vzduch